Implementasi Teorema Bayes pada Sistem Pakar untuk Mendiagnosis Penyakit pada Tanaman Tomat - Yuliana Febriyanti Tefa; Darsono Nababan; Yasinta Oktaviana Legu Rema; Hevi Herlina Ullu (Fakultas Pertanian, Universitas Timor, 2022)
The number of diseases in tomatoes today can make farmers confused in determining or choosing the type of treatment that suits the tomato disease. This what makes farmers in K district North Central Timor it's hard to get results because they can't consult with experts , so that the level of productivity decreases. -based expert system web can be used to solve problems in terms of helping each farmer in dealing with pests and diseases . The method used in diagnosing is disease in tomato plants is a method bayes theorem , where each alternative provided will be give the value of the hypothesis to get the best results. Hypothesis value in tomato disease ranges from 1 to 0.1 where for hypothesis value 1 is a hypothetical value which shows that the results of this value prove that tomato plants are very specific to diseases and pests while hypothesis value 0.1 indicates that there is no specific for pests and diseases but is found in other diseases. From the results of the study it can be concluded that the system expert which is built is expected to be able to help farmers in Diagnosing diseases and pests on tomato plants in accordance with calculation results bayes obtained.